Fatigue in a simulated cross-country skiing sprint competition - Vesterinen, V.; Mikkola, J.; Nummela, A.; Hynynen, E.; Häkkinen, K. (Journal of Sports Sciences, 2009)
The aim of this study was to assess fatigue during a simulated cross-country skiing sprint competition based on skating technique. Sixteen male skiers performed a 30-m maximal skiing speed test and four 850-m heats with roller skies on a tartan track, separated by 20 min recovery between heats. Physiological variables (heart rate, blood lactate concentration, oxygen consumption), skiing velocity, and electromyography (EMG) were recorded at the beginning of the heats and at the end of each 200-m lap during the heats. Maximal skiing velocity and EMG were measured in the speed test before the simulation. No differences were observed in skiing velocity, EMG or metabolic variables between the heats. The end (820-850 m) velocities and sum-iEMG of the triceps brachii and vastus lateralis in the four heats were significantly lower than the skiing velocity and sum-iEMG in the speed test. A significant correlation was observed between mean oxygen consumption and the change in skiing velocity over the four heats. Each single heat induced considerable neuromuscular fatigue, but recovery between the heats was long enough to prevent accumulation of fatigue. The results suggest that the skiers with a high aerobic power were less fatigued throughout the simulation.